(untitled) (Journal of Parents and Teachers, 1996)
Victor Sazfiego, inventor of the LUDIBOX, has overcome numerous personal and professional challenges to foster creativity and spatial vision in children and adults. Through his work in schools, hospitals and other settings, he seeks to provide meaningful and socially useful experiences. Despite the challenges, his dedication and perseverance are fundamental to his work.